Hypoxia-targeted radiotherapy dose painting for head and neck cancer using 18F-FMISO PET: A biological modeling study. (November 2013) - Chang, Joe H.; Wada, Morikatsu; Anderson, Nigel J.; Lim Joon, Daryl; Lee, Sze Ting; Gong, Sylvia J.; Gunawardana, Dishan H.; Sachinidis, John; O'Keefe, Graeme; Gan, Hui K.; Khoo, Vincent; Scott, Andrew M.
Abstract Background. This study investigates the use of 18F-fluoromisonidazole (FMISO) PET-guided radiotherapy dose painting for potentially overcoming the radioresistant effects of hypoxia in head and neck squamous cell carcinoma (HNSCC). Material and methods. The study cohort consisted of eight patients with HNSCC who were planned for definitive radiotherapy. Hypoxic subvolumes were automatically generated on pre-radiotherapy FMISO PET scans. Three radiotherapy plans were generated for each patient: a standard (STD) radiotherapy plan to a dose of 70 Gy, a uniform dose escalation (UDE) plan to the standard target volumes to a dose of 84 Gy, and a hypoxia dose-painted (HDP) plan with dose escalation only to the hypoxic subvolume to 84 Gy. Plans were compared based on tumor control probability (TCP), normal tissue complication probability (NTCP), and uncomplicated tumor control probability (UTCP). Results. The mean TCP increased from 73% with STD plans to 95% with the use of UDE plans (p < 0.001) and to 93% with HDP plans (p < 0.001). The mean parotid NTCP increased from 26% to 44% with the use of UDE plans (p = 0.003), and the mean mandible NTCP increased from 2% to 27% with the use of UDE plans (p = 0.001). There were no statistically significant differences between any of the NTCPs between the STD plans and HDP plans. The mean UTCP increased from 48% with STD plans to 66% with HDP plans (p = 0.016) and dropped to 37% with UDE plans (p = 0.138). Conclusion. Hypoxia-targeted radiotherapy dose painting for head and neck cancer using FMISO PET is technically feasible, increases the TCP without increasing the NTCP, and increases the UTCP. This approach is superior to uniform dose escalation.